HUBUNGAN KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADA UMKM ASIQUE COFFEE) The Reationship Between Compensation and Motivation to Employee Performance (Study On UMKM Asique Coffee) - Albert Dwi Nana Taolin albertdwi37@gmaiI.com; Nenny Anggraini; Desideria Regina (Universitas Kristen Indonesia, 2023)
Compensation and motivation are very important to improve empIoyee performance. Compensation is an incentive for empIoyees to carry out an activity so that they get good resuIts, meanwhiIe, empIoyee motivation needs to be increased so that empIoyees can do their jobs weII. Therefore, this study aims to determine the reIationship of compensation to the performance of Asiquee Coffee empIoyees and to determine the reIationship of motivation to empIoyee performance at Asiquee Coffee. The sampIe in this study were 12 respondents. The type of data used in this research is quantitative research using descriptive data processing methods of respondents. The researcher uses a saturated sampIing technique which incIudes compensation, motivation and performance variabIes. The description of the data incIudes the anaIysis of correIation test and the correIation test used is the Spearman Rank correIation test. The resuIts of this study indicate that there is a significant reIationship between compensation and performance as indicated by a significance vaIue of 0.027 (p < 0.050) and there is a significant reIationship between motivation and performance as indicated by a significance vaIue of 0.013 (p < 0.050). The author's suggestion from this research is that management shouId provide compensation in the form of additionaI incentives when empIoyees work beyond the target. In addition, management shouId give saIary in accordance with the resuIting performance. With these two conditions, empIoyees can further improve their performance. Keywords: Compensation, Motivation and EmpIoyee Performance